PELATIHAN KETRAMPILAN DASAR BAGI KADER PALIATIF KANKER DI DKI JAKARTA - Widani, Ni Luh (Jurnal Abdimas Musi Charitas, 2020)
Cancer is a non-contagious chronic disease that affects physical, psychological, social and spiritual conditions, and in terminal conditions it requires assistance in fulfilling hygiene. Community empowerment by the Yayasan Kanker Indonesia in the DKI Jakarta Region through the formation of a cancer palliative health cadre. Dedication activities for 85 Jakarta palliative health cadres and divided into two periods: the first period is on 5 until 8 November 2019 with 43 people and the second period on 12 until 15 November 2019 and followed by 42 people, at 08.00 a.m. – 17.00 p.m. The activity aims to provide basic knowledge and skills in caring for cancer patients to be able to provide care, referral and reporting of cancer patients in their area. The method used lectures, simulations and demonstrations is divided into six groups each period. As a result all participants took part in the full activities with satisfying results with Good scores for all the skills tested. In conclusion, training for cancer palliative cadres needs to be provided with a small group so that participants can practice all the skills and can be evaluated directly by the facilitator.